A pragmatic approach to the diagnosis of nodal micrometastases in early stage non-small cell lung cancer - Herpel, Esther; Muley, Thomas; Schneider, Thomas; Palm, Elisa Maria; Kieslich de Hol, Dörthe; Warth, Arne; Meister, Michael; Storz, Konstantina; Schnabel, Philipp Albert; Schirmacher, Peter; Dienemann, Hendrik; Hoffmann, Hans (Journal of thoracic oncology, 2010)
Introduction - This study was designed to develop a both sensitive and efficient algorithm for detection of lymph node micrometastases and to determine its prognostic impact in patients with early stage non-small cell lung cancer (NSCLC). - Methods - One hundred seventy patients with NSCLC p stage I and II were included in this study, of which n = 5299 lymph nodes were obtained and submitted to histopathologic analysis. From each patient, a median number of 31 lymph nodes was received (N-1 position: median n = 16; N-2 position: median n = 15). Immunohistochemistry was performed to detect micrometastases unobvious by conventional microscopy using antibodies against cytokeratins (CK) (pan-CK: KL-1, CK 5/6, CK 7) and the epithelial marker Ber-EP4. - Results - In 82 patients (48.2%), micrometastases were revealed in immunohistochemistry staining. KL-1 detected micrometastases in 201 (99.5%) of 202 positive lymph nodes. Subsequently, this resulted in an upstaging in 39 patients (20.5%). Detection of micrometastases in otherwise tumor-free N2-lymph nodes had a significant prognostic impact (mean disease-free survival 21.4 versus 45.3 months, p = 0.022), affecting 4.7% of patients. Survival differences between patients who were upstaged into stage II (N0>N1) and those remaining in stage I were not statistically significant (p = 0.537). - Conclusion - Extended workup of N2-lymph nodes using one broad-spectrum keratin marker in otherwise N2-negative lymph nodes may represent a both efficient and sensitive approach to the identification of micrometastases in dissected lymph nodes of patients with early stage NSCLC.